Charged, but found "not guilty": innocence of the suspect bridging ligands [RO(O)CNNC(O)OR]2- = L2- in [(acac)2Ru(μ-L)Ru(acac)2]n, n = +,0,-,2 - Roy, Sayak; Sarkar, Biprajit; Imrich, Hans-Georg; Fiedler, Jan; Záliš, Stanislav; Jimenez-Aparicio, Reyes; Urbanos, Francisco A; Mobin, Shaikh M; Lahiri, Goutam Kumar; Kaim, Wolfgang (Inorganic chemistry, 2012)
Neutral diastereoisomeric diruthenium(III) complexes, meso- and rac-[(acac)(2)Ru(μ-adc-OR)Ru(acac)(2)] (acac(-) = 2,4-pentanedionato and adc-OR(2-) = dialkylazodicarboxylato = [RO(O)CNNC(O)OR](2-), R = tert-butyl or isopropyl), were obtained from electron transfer reactions between Ru(acac)(2)(CH(3)CN)(2) and azodicarboxylic acid dialkyl esters (adc-OR). The meso isomer 3 with R = isopropyl was structurally characterized, revealing two deprotonated and N-N coupled carbamate functions in a reduced dianionic bridge with d(N-N) = 1.440(5) Å. A rather short distance of 4.764 Å has been determined between the two oxidized, antiferromagnetically coupled Ru(III) centers. The rac isomer 4 with R = isopropyl exhibited stronger antiferromagnetic coupling. While the oxidation of the neutral compounds was fully reversible only for 3 and 4, two well-separated (10(8) < K(c) < 10(10)) reversible one-electron reduction steps produced monoanionic intermediates 1(-)-4(-) with intense (ε ≈ 3000 M(-1) cm(-1)), broad (Δν(1/2) ≈ 3000 cm(-1)) absorptions in the near-infrared (NIR) region around 2000 nm. The absence of electron paramagnetic resonance (EPR) signals even at 4 K favors the mixed-valent formulation Ru(II)(adc-OR(2-))Ru(III) with innocently behaving bridging ligands over the radical-bridged alternative Ru(II)(adc-OR(•-))Ru(II), a view which is supported by the metal-centered spin as calculated by density functional theory (DFT) for the methyl ester model system. The second reduction of the complexes causes the NIR absorption to disappear completely, the EPR silent oxidized forms 3(+) and 4(+), calculated with asymmetrical spin distribution, do not exhibit near infrared (NIR) activity. The series of azo-bridged diruthenium complex redox systems [(acac)(2)Ru(μ-adc-R)Ru(acac)(2)](n) (n = +,0,-,2-), [(bpy)(2)Ru(μ-adc-R)Ru(bpy)(2)](k) (k = 4+,3+,2+,0,2-), and [(acac)(2)Ru(μ-dih-R)Ru(acac)(2)](m) (m = 2+,+,0,-,2-; dih-R(2-) = 1,2-diiminoacylhydrazido(2-)) is being compared in terms of electronic structure and identity of the odd-electron intermediates, revealing the dichotomy of innocent vs noninnocent behavior.